Promoting Reading Comprehension Among English Language Learners: KWLS Technique - Surti Milarisa (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2020)
Reading is a complex linguistic process in which students have a deeper knowledge of how to interpret reading texts. Teachers need some informative methods to stimulate student motivation in the learning process to improve students reading capabilities. Based on the research purpose, the researcher decided to implement the KWLS technique at STIE Muhammadiyah Tanjung Redeb East Borneo. This study was Classroom Action Research (CAR) which covered standardized indicators suggested by Kemmis and McTaggart, including planning, observing, implementing, and reflecting. As the results of this research, it indicated that the technique can provide an opportunity for students to develop their reading comprehension and to meet a minimum standard of passing. After conducting the study, the researcher found that the KWLS technique was very successful in increasing students' reading comprehension. The improvements in the student's passing grade have been revealed or no student with a low score in the second cycle.